High stress twinning in a compositionally complex steel of very high stacking fault energy - Wang, Zhangwei; Lu, Wenjun; An, Fengchao; Song, Min; Ponge, Dirk; Raabe, Dierk; Li, Zhiming (Nature communications, 2022)
Deformation twinning is rarely found in bulk face-centered cubic (FCC) alloys with very high stacking fault energy (SFE) under standard loading conditions. Here, based on results from bulk quasi-static tensile experiments, we report deformation twinning in a micrometer grain-sized compositionally complex steel (CCS) with a very high SFE of ~79 mJ/m 2 , far above the SFE regime for twinning (<~50 mJ/m 2 ) reported for FCC steels. The dual-nanoprecipitation, enabled by the compositional degrees of freedom, contributes to an ultrahigh true tensile stress up to 1.9 GPa in our CCS. The strengthening effect enhances the flow stress to reach the high critical value for the onset of mechanical twinning. The formation of nanotwins in turn enables further strain hardening and toughening mechanisms that enhance the mechanical performance. The high stress twinning effect introduces a so far untapped strengthening and toughening mechanism, for enabling the design of high SFEs alloys with improved mechanical properties. Mechanical twinning is difficult to trigger in face centered cubic alloys with high stacking fault energies (SFEs) under standard tensile loading. Here, the authors report high stress twinning in a bulk compositionally complex steel of very high SFE, enhancing the material’s mechanical performance.